2016
DOI: 10.1007/s11270-016-2836-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulfate Application on Inhibiting Accumulation and Alleviating Toxicity of Arsenic in Panax notoginseng Grown in Arsenic-Polluted Soil

Abstract: Panax notoginseng (P. notoginseng) is a well-known traditional Chinese medicinal herb. Due to elevated arsenic (As) levels in some planting area, P. notoginseng and its derivatives are contaminated, and the As concentration in these products exceeds the standard limit (As concentration < 2 mg/kg). In this study, the effects of sulfate (S) application on As uptake and the physicological response of P. notoginseng were investigated in a pot-culture experiment. The results showed that the As concentration in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…26 However, routine hot acid digestion of rice grains leads to transformation of DMMTA to DMA and therefore underestimation of a highly toxic species which is not regulated by the current As rice grain standards. 25 Based on the observed spontaneous thiolation of methylated oxyarsenates, it is to be expected that agronomic practices that have a potential to increase As methylation, such as the soil incorporation of crop residues 8 and sulfate-based fertilization, 48 may also increase the exposure of rice plants to DMMTA.…”
Section: ■ Discussionmentioning
confidence: 99%
“…26 However, routine hot acid digestion of rice grains leads to transformation of DMMTA to DMA and therefore underestimation of a highly toxic species which is not regulated by the current As rice grain standards. 25 Based on the observed spontaneous thiolation of methylated oxyarsenates, it is to be expected that agronomic practices that have a potential to increase As methylation, such as the soil incorporation of crop residues 8 and sulfate-based fertilization, 48 may also increase the exposure of rice plants to DMMTA.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Bright et al showed that sulfate-reducing as well as fermentative and/or methanogenic cultures enriched from lake sediments produced more methylated arsenic than iron- or manganese-reducing cultures. Mikutta and Rothwell showed that 82% of the As in a sulfate- and As-impacted peat bog was present as organoarsenic species, and Zeng et al showed that the abundance of methylated As in the roots of a ginseng plant increased 263% following soil amendment with sulfate (SO 4 2– ). These studies collectively suggest that sulfur and/or sulfate reduction stimulates the biotransformation of As into methylated products, and this hypothesis is supported by functional gene array studies documenting abundant arsM sequences from SRB in soils from Asia, the U.K., and the U.S. , If true, this active role for SRB in arsenic methylation would parallel the well-documented role of SRB as key methylators of mercury in aquatic environments. Links between SRB and arsenic methylation have not, to our knowledge, been rigorously tested.…”
Section: Introductionmentioning
confidence: 98%
“…Bright et al 30 showed that sulfatereducing as well as fermentative and/or methanogenic cultures enriched from lake sediments produced more methylated arsenic than iron-or manganese-reducing cultures. Mikutta and Rothwell 31 showed that 82% of the As in a sulfate-and Asimpacted peat bog was present as organoarsenic species, and Zeng et al 32 showed that the abundance of methylated As in the roots of a ginseng plant increased 263% following soil amendment with sulfate (SO 4 …”
Section: ■ Introductionmentioning
confidence: 99%
“…Other studies have reported an increase in As methylation efficiency after the amendment of sulphate [79] or organic matter to soil [15,[80][81][82], or after the increase in dissolved organic carbon in soil [83]. The positive impact of sulphate amendment on As methylation was interpreted as pointing to the role of SRB in As methylation [79].…”
Section: Discussionmentioning
confidence: 97%